Factors Affecting Employee Performance: A Systematic Review - Fadli Agus Triansyah; Wang Hejin; Stuparu Stefania (Yayasan Adra Karima Hubbi, 2023)
Employee performance is one of the key factors in achieving organizational goals. Employee performance is a measure of the extent to which an employee is able to fulfill his duties and responsibilities properly and effectively. This study utilised a systematic review factors affecting employee performance scopus database. A systematic review is a form of research study that seeks to answer a particular research question by systematically identifying, selecting, and evaluating all relevant evidence. After conducting the screening, the researchers found 7 articles that met the predetermined criteria. The focus of research on factors affecting employee performance are focuses on several things such as trade organizations, motivation, management system, key performance indicators, perceived overqualification, chefs, continuous improvement, system dynamics model, implementation of performance management, the level of pay, the offer of benefits and job satisfaction. Based on some of the results of research that has been done, we can conclude that employee performance is very important because employee performance plays a very important role in achieving organizational goals. Therefore, companies must prioritize managing employee performance in order to increase productivity, efficiency, and the quality of work produced.